2016
DOI: 10.1038/ncomms11436
|View full text |Cite
|
Sign up to set email alerts
|

Analytic framework for peptidomics applied to large-scale neuropeptide identification

Abstract: Large-scale mass spectrometry-based peptidomics for drug discovery is relatively unexplored because of challenges in peptide degradation and identification following tissue extraction. Here we present a streamlined analytical pipeline for large-scale peptidomics. We developed an optimized sample preparation protocol to achieve fast, reproducible and effective extraction of endogenous peptides from sub-dissected organs such as the brain, while diminishing unspecific protease activity. Each peptidome sample was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
119
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(123 citation statements)
references
References 38 publications
4
119
0
Order By: Relevance
“…Recently, Secher et al 42 reported on an analytical framework for peptide characterization using the longest peptide variant (LPV) method, where peptides were assembled into LPVs to account for the sequential degradation ladder sequences due to non-specific enzymatic activity. Using this approach, 14,416 unique peptide sequences were grouped into 2,835 LPVs, of which 356 were derived from prohormone precursors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Secher et al 42 reported on an analytical framework for peptide characterization using the longest peptide variant (LPV) method, where peptides were assembled into LPVs to account for the sequential degradation ladder sequences due to non-specific enzymatic activity. Using this approach, 14,416 unique peptide sequences were grouped into 2,835 LPVs, of which 356 were derived from prohormone precursors.…”
Section: Resultsmentioning
confidence: 99%
“…Though the mass spectrometric platforms used in both studies are different, we posit that the principal factor contributing to this dissimilarity could be the difference in the peptide extraction method used. Secher et al 42 used urea, which is a preferred choice for protein extraction as it helps dissolve the protein, but may not be optimal for peptides, especially as peptides are smaller and more easily dissolvable compared to proteins. Moreover, the otherwise insoluble proteins would now be soluble, with a potential to degrade during sample processing, and thus can mask some of the trace-level endogenous peptides.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other differences could be explained by the relative immaturity of hPSC-derived hypothalamic neurons at the time points we studied, resulting in incomplete pro-peptide processing or expression at levels too low to be automatically detectable using the automated peptide identification pipeline we employed. The use of more sensitive LC-MS/MS instruments or the analysis of raw peptidomic data using new discovery tools 69 may reveal further biologically important peptides. We found that exposure of hPSC-derived hypothalamic neurons to leptin significantly increased the concentration of both a-MSH and b-MSH, and that these peptides were robustly secreted from upon stimulation.…”
mentioning
confidence: 99%